KEBIJAKAN PRESIDEN AMERIKA SERIKAT DONALD TRUMP KELUAR DARI PARIS AGREEMENT (COP-21) - BerylBeryl Rifqi Alhadi; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research discusses about “Donald Trump’s policy withdraw Paris Agreement (COP-21) 2015”. The purpose is this research is to find out why Donald Trump withdraw from paris agreement. The Paris Agreement’s central aim is to strengthen the global response to the threat of climate change by keeping a global temperature rise this century well below 2 degrees Celsius above pre-industrial levels and to pursue efforts to limit the temperature increase even further to 1.5 degrees Celsius. Donald Trump pull out from the paris agreement because three factors, individu of Donald Trump, oil, gas, and coal companys, and republican party.This is qualitative research which used descriptive explanative methods, and collecting datas from books, journals, articles, mass media, official ublications and relevant websites. This paper used the idiosyncratic concept written by James N. Rosenau and Alex Mintz , analysis unit individu and the theory is behavariolism written Richard C. SnyderThe result of the research is Donald Trump pull out from paris agreement beacause three factors, individu of Donald Trump, oil, gas, coal companys, and republican party. Donald Trump believes climate change is a hoax. oil, gas, and coal companys has strong influence over Donald Trump decision , they have incredible amount of money , from lobbying and campaign contributor for Trump and Republican congress. Republican member party also has strong influence over donald Trump decision.Key words : Paris Agreement, , republican party, lobbying, campaign contributor